The Study of "Affiliation" a pertinent social motive among tribal and non-tribal college students of Assam - Baruah, Dr Manidipa (International Journal of Scientific Research and Management (IJSRM), 2014)
The current research study investigates the motivational pattern viz Affiliation motivation among the tribal students of Assam. The sample consisted of 240 college students (120 tribal and 120 non-tribal) ranging from18-24 years, 60 males and 60 females for both tribal and non-tribal. Attempts were made to include all the prominent tribes of Assam viz. Bodo Kachari, karbi, Miris, Lalung, Dimasa Kachari and Rabhas, Thematic Apperception Test and semi structured interview schedule were administered for information about their family types, parental deprivation, parental relations, social and political belongingness. Mean, Standard Deviation, and t-test were the statistical measures adopted in this 2x2 factorial design study. In addition to this discriminant analysis has been worked out to strengthen the predictive validity of the obtained data. TAT scores reveal significant difference between the tribal’s and non-tribal on Affiliation motivation. However results obtained on gender difference indicates dissimilar scores among both the cultures .Results depict that tribal college students possess low affiliative tendency as compared to non-tribal .Further n-affiliation was studied on two directions n-associative and n-emotional. Similar trend of results was seen for the two directions showing significant difference in both culteres .Scores on discriminent analysis depict that nemotional (.227)is the dependent measure which has the most discriminating affiliative tendency among both the cultures